Mediasi Sebagai Salah Satu Alternatif Penasihatan Keluarga Bermasalah - Achmad Asfi Burhanudin; Muhammad Al Faruq (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
The sakinah family full of mawaddah and rahmah is everyone's dream. A sakinah family can be built if every element of the family, especially husband and wife, understands the purpose of marriage and works out their respective rights and obligations. They love each other, love, respect, and help each other both outwardly and mentally. They understand each other and appreciate each other's positions and functions. If this all goes well, then a serene happy family, full of love and affection, will automatically form in their family. The problem is, if every element in the family, especially husband and wife, does not understand and implement all of it well, then their family becomes a family that is problematic, full of slander, full of prejudice, not harmonious, and finally the family cannot be maintained. Indeed, there has never been a family without strife and differences. Therefore, the advisory factor becomes very important in order to get the family back on track. New patterns of counseling troubled families that can be developed in Indonesia need to be continuously studied and tested for reliability. While we use and perfect the old pattern, this new pattern needs serious attention, especially from BP4 which is very experienced and known as a leading marriage advisory agency in Indonesia. The essence of the Supreme Court Regulation of the Republic of Indonesia Number 1 of 2008 concerning Mediation Procedures in Court is what the Minister of Religious Affairs and his staff have wanted since decades ago. The nature of what is desired is that the advisory role performed by professional institutions outside the court – in this case BP4 – can be enlarged, so that the number of broken families can be minimized as much as possible